2017
DOI: 10.1038/s41598-017-02928-1
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12 and osteopontin from bone marrow-derived mesenchymal stromal cells improve muscle regeneration

Abstract: Muscle satellite cells are essential for muscle regeneration. However, efficient regeneration does not occur without muscle-resident mesenchymal progenitor cells. We show here that bone marrow-derived mesenchymal stromal cells (Bm-MSCs) also facilitate muscle regeneration in Duchenne muscular dystrophy (DMD) model mice. Bm-MSCs transplanted into peritoneal cavities of DMD model mice with severe muscle degeneration strongly suppressed dystrophic pathology and improved death-related symptoms, which resulted in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 49 publications
3
51
1
Order By: Relevance
“…Our hypothesis on the regenerative potential of MSCs of BM origin in muscular dystrophies is also supported by very recent studies by Maeda et al ( 2017 ). The authors documented that transplantation of MSCs of BM origin into peritoneal cavities of a mdx mouse model strongly suppressed dystrophic pathology in diaphragms of mdx deficient mice, which resulted in significant lifespan extension.…”
Section: Combined Therapy With Mscs Of Bm Origin and Scs Of Skeletal supporting
confidence: 87%
See 1 more Smart Citation
“…Our hypothesis on the regenerative potential of MSCs of BM origin in muscular dystrophies is also supported by very recent studies by Maeda et al ( 2017 ). The authors documented that transplantation of MSCs of BM origin into peritoneal cavities of a mdx mouse model strongly suppressed dystrophic pathology in diaphragms of mdx deficient mice, which resulted in significant lifespan extension.…”
Section: Combined Therapy With Mscs Of Bm Origin and Scs Of Skeletal supporting
confidence: 87%
“…Biological properties of MSCs provide an even wider tool with regenerative potential, as previously documented by their well-predicted therapeutic application in tissue regeneration of post-infarct heart (Jung et al 2017 ; van den Akker et al 2013 ). The immunomodulatory potential of MSCs is not only desired in the well-known therapy of graft-versus-host disease, and serious complications in patients after hematopoietic stem cell transplantation (Copland et al 2015 ; Le Blanc et al 2004 ; Lin and Hogan 2011 ), but also proved to be beneficial in therapy for skeletal, muscular (Maeda et al 2017 ) and neural regeneration (Mokarram et al 2012 ).…”
Section: Mscs Of Bone Marrow Originmentioning
confidence: 99%
“…Since we saw decreased levels of inflammation in the A . cahirinus TA during regeneration we looked at levels of Cxcl12 , a chemokine that has been shown to have a novel anti-inflammatory role 33 , as well as a role in positively regulating muscle regeneration 34 , 35 . The change in expression of Cxcl12 was greater in A .…”
Section: Resultsmentioning
confidence: 99%
“…musculus because of the lack of induction of inflammation and fibrosis pathways and in support of this we found that A . cahirinus expressed higher levels of Cxcl12 , a cytokine with a known anti-inflammatory role 33 and a role in positively regulating muscle regeneration 34 , 35 . Identifying cytokines such as this may well provide the molecular explanation for the improved muscle regenerative capacities of A .…”
Section: Discussionmentioning
confidence: 99%
“…Mesenshymal stem/progenitor cells (MSC/MPC) are also expected to be a tool for regenerative medicine. They themselves do not differentiate into myofibers, but support muscle regeneration by paracrine effects [11]. The history of direct reprogramming in the muscle field is long, starting with the discovery of MyoD by Weintraub and his colleagues [12,13].…”
Section: Muscle Stem Cellsmentioning
confidence: 99%